KNOWLEDGE, PERCEPTION, AND STIGMA IN THE JAKARTA COMMUNITY TOWARD TUBERCULOSIS PREVENTION - Rahmawati, Apriana; Wulandari, Shenda Maulina; Milanti, Ariesta; Efendi, Ferry; Maryuni, Maryuni; Mutia, Jeihan; Aprilia, Nur Ravica (The Indonesian Journal of Public Health, 2024)
Introduction: The Corona Virus Infectious Disease (COVID)-19 pandemic has impacted tuberculosis (TB) diagnosis and treatment in Indonesia, making Indonesia rank second in the world’s tuberculosis cases. Tuberculosis epidemiology worsened during the pandemic; an estimated 10.6 million people fell ill with tuberculosis worldwide in 2021, an increase of 4.5% from the previous year (Falzon et al., 2023). Aims: The purpose of this study was to determine the relationship between knowledge, perception, and stigma toward tuberculosis prevention in the community in Jakarta. Methods: Respondents in this study were selected using simple random sampling with the criteria at least 17 years of age and currently not diagnosed as a TB patient. Those who were diagnosed with active TB and were on treatment were excluded from the study. Using a cross-sectional design, this study was analyzed with logistic regression. Results: Two factors were found to be associated with the level of tuberculosis prevention behavior. Respondents with better knowledge about tuberculosis were 5.13 times more likely to make good prevention in tuberculosis (OR=5.129; 95% CI=2.341-11.238; p-value <0.001). In addition, having a positive perception of tuberculosis prevention was also associated with better tuberculosis prevention practices (OR=3.301; 95% CI=1.402-7.772; p-value=0.006). Conclusion: Knowledge and perceptions can also eventually lead to stigma, which results in delayed diagnosis, increases the source of transmission, and hinders efforts to reduce its prevalence. A possible recommendation is to educate the community about TB transmission, treatment, and prevention to dispel myths and negative perceptions.